Analisis Implementasi Backward Design pada Kelas Industri terhadap Motivasi Karir Peserta Didik SMKN 33 Jakarta - Wajdi, Farelina; Al Ghiffari, Muhammad Fajry (Program Studi Pendidikan Vokasi Seni Kuliner, 2026)
This study examines the implementation of industrial classes using the Backward Design approach at SMK Negeri 33 Jakarta and its impact on students' career motivation. The Merdeka Curriculum provides flexibility for teachers to design project-based learning according to the needs of the world of work. Through industrial cooperation with PT. Jaddi Foods Group, students gain direct experience in the field of pastry and bakery, thereby improving their practical skills and work readiness. Backward Design is used to ensure that learning objectives are achieved systematically, starting from determining the final outcome, determining the assessment, to planning the learning. The results of the implementation show that students' motivation, interest, and confidence have increased. Supporting factors include collaboration between schools and industry; obstacles include limited facilities and curriculum adaptation. This study recommends sustainable strategies to strengthen the synergy between vocational education and the industrial world.